1998
DOI: 10.1126/science.282.5393.1504
|View full text |Cite
|
Sign up to set email alerts
|

Local GABA Circuit Control of Experience-Dependent Plasticity in Developing Visual Cortex

Abstract: Sensory experience in early life shapes the mammalian brain. An impairment in the activity-dependent refinement of functional connections within developing visual cortex was identified here in a mouse model. Gene-targeted disruption of one isoform of glutamic acid decarboxylase prevented the competitive loss of responsiveness to an eye briefly deprived of vision, without affecting cooperative mechanisms of synapse modification in vitro. Selective, use-dependent enhancement of fast intracortical inhibitory tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
741
5
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 820 publications
(779 citation statements)
references
References 84 publications
32
741
5
1
Order By: Relevance
“…Inhibition is well known to have a crucial role in the expression and regulation of neural plasticity during development and adulthood: there is evidence, indeed, that the inhibitory tone is essential for the time course of critical period in the visual cortex 16 and it has been demonstrated that strategies decreasing inhibition reactivate developmental levels of plasticity in the adult brain 17 . We quantified the extracellular levels of γ-aminobutyric acid (GABA) and glutamate in the binocular visual cortex of FR and CTL animals using in vivo brain microdialysis and high-performance liquid chromatography (HPLC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition is well known to have a crucial role in the expression and regulation of neural plasticity during development and adulthood: there is evidence, indeed, that the inhibitory tone is essential for the time course of critical period in the visual cortex 16 and it has been demonstrated that strategies decreasing inhibition reactivate developmental levels of plasticity in the adult brain 17 . We quantified the extracellular levels of γ-aminobutyric acid (GABA) and glutamate in the binocular visual cortex of FR and CTL animals using in vivo brain microdialysis and high-performance liquid chromatography (HPLC).…”
Section: Resultsmentioning
confidence: 99%
“…Diazepam enhances GABA receptor-mediated current, and is a common tool used for enhancing inhibition in the cerebral cortex 16 . We measured binocularity in monocularly deprived FR rats treated with diazepam by recording C/I VEP ratio in the visual cortex contralateral to the deprived eye.…”
Section: Resultsmentioning
confidence: 99%
“…BDNF is known to modulate the development and plasticity of the visual cortex (Huang et al, 1999) possibly by regulating the GABAergic inhibitory system, which has a clear role in cortical development (Hensch et al, 1998). We measured BDNF protein and glutamic acid decarboxylase (GAD) 65/67 expression and found that enrichment transiently increases levels of BDNF protein and GAD65/67 expression in the occipital cortex of EC with respect to SC animals before postnatal day (P) 15.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic reduction of intracortical GABA release blocks the effects of MD that can be restored by local pharmacological enhancement of GABA signaling (3,4). Accelerating the rate of inhibitory cell maturation leads to a precocious period of plasticity (5).…”
mentioning
confidence: 99%